Home-based self-administered transcranial direct current stimulation for women affected by primary dysmenorrhoea in Northeastern Brazil: a protocol study - Thiago Anderson Brito De Araújo; Edson Silva-Filho; Rodrigo Pegado; Tatiana Camila de Lima Alves da Silva; Yvinna Tamiris Rodrigues; Paloma Cristina Alves de Oliveira; Ervinas Bernatavicius; Alexander Anthony Cook; Emilè Radytè; Maria Thereza Micussi (BMJ Open, 2025)
Background The prevalence of women with primary dysmenorrhoea is high and negatively impacts physical and mental health. The intense cyclic episodes of pain generate central nervous system dysfunctional processing. In this sense, strategies focused on the central nervous system are important to re-establish normal functioning. Home-based self-administered transcranial direct current stimulation (tDCS) emerges as a strategy to modulate dysfunctional brain areas and improve the symptoms. This protocol aims to evaluate the effects of home-based self-administered tDCS for pain, premenstrual symptoms, physical performance, quality of life, electroencephalography and patient global impression in women affected by primary dysmenorrhoea.Methods and analysis This is a single-centre, parallel, randomised, double-blinded clinical trial protocol. 40 women affected by primary dysmenorrhoea will be randomised into two groups (active-tDCS or sham-tDCS). Then, 20 consecutive sessions of home-based self-administered tDCS will be performed. The assessments will occur at five time points: baseline, after the 20th sessions, at the first, second and third cycles after tDCS interventions (follow-ups). Primary outcome will be pain according to visual analogue scale. Quality of life, premenstrual symptoms screening, depression, anxiety, physical performance, electroencephalography and participants’ satisfaction will be the secondary outcomes. A mixed analysis of variance will calculate the effect of stimulation.Ethics and dissemination The study was approved by the ethics committee of the Federal University of Rio Grande do Norte (No. 6.037.756) and registered in the Brazilian Clinical Trials Registry (n° RBR-747k8vb). Participants may withdraw at any time without penalty. Free support will be available from the lead researcher if needed. All procedures will follow Good Clinical Practice and international ethical standards.Trail registration https://ensaiosclinicos.gov.br/rg/RBR-747k8vb